Complex roles of myoglianin in regulating adult performance and lifespan. Issue 4 (2nd October 2017) - Augustin, Hrvoje; Adcott, Jennifer; Elliott, Christopher J. H.; Partridge, Linda
ABSTRACT: Myoglianin, the Drosophila homolog of the secreted vertebrate proteins Myostatin and GDF-11, is an important regulator of neuronal modeling, and synapse function and morphology. While Myoglianin suppression during development elicits positive effects on the neuromuscular system, genetic manipulations of myoglianin expression levels have a varied effect on the outcome of performance tests in aging flies. Specifically, Myoglianin preserves jumping ability, has no effect on negative geotaxis, and negatively regulates flight performance in aging flies. In addition, Myoglianin exhibits a tissue-specific effect on longevity, with myoglianin upregulation in glial cells increasing the median lifespan. These findings indicate complex role for this TGF-β-like protein in governing neuromuscular signaling and consequent behavioral outputs and lifespan in adult flies.